PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR (STUDI EMPIRIS SUB SEKTOR MAKANAN DAN MINUMAN PERIODE 2021-2023) - Putri, Mutiara Sani; Dewi, Putu Pande R. Aprilyani; Kusuma, Putu Sri Arta Jaya; Widiantari, Komang Sri (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
The increase in domestic consumption, particularly in the food and beverage subsector, has contributed to the growth of Indonesia's economy. Among the most crucial economic sectors in Indonesia is the food industry. This study examines the execution of good corporate governance as a factor influencing the financial performance of companies. Good Corporate Governance (GCG) is defined as the division of responsibilities between shareholders, supervisors, and stakeholders in managing the company. GCG aims to enhance the company's value and ensure that each party has clear responsibilities. The objective of this study is to determine the effect of the board of commissioners, the board of directors, managerial ownership, and institutional ownership on financial performance. The research uses secondary data, with a sample size of 55 manufacturing companies in the food and beverage sub-sector for the period of 2021-2023. The analytical technique used is multiple linear regression. According to the study's outcomes, the board of commissioners has a positive and significant effect on financial performance. The board of directors has a positive and significant effect on financial performance. Managerial ownership has a positive and significant effect on financial performance. Institutional ownership has a positive and significant effect on financial performance